Marriage patterns between social layers in Tana Toraja Regency - Supriadi Torro; Yenni Misi’; Zinal Arifin; La Sunra (Technium Social Sciences Journal, 2023)
This study aims to determine: 1) the differences in marriage patterns between social strata in traditional and modern times in Makale District, Tana Toraja Regency, and 2) the impact that occurs from shifting marriage traditions. This research is qualitative in nature using descriptive approach. The research was conducted using purposive sampling technique. 10 informants were selected by using the criteria: (a) families that have married their children more than once, (b) representing lower-class criteria, (c) representing upper-class criteria, and (d) representing position in religion. Data collection techniques are observation, documentation, and interviews. Checking the validity of the data is done by member check. Data analysis stages include data condensation, data presentation, and conclusion drawing and data verification. The results of this study indicate that 1) there are differences in the pattern of marriage between social strata in traditional and modern times in Makale District, Tana Toraja Regency. (a) In traditional times, only men from the upper-class may marry lower-class women. (b) In modern time, a specific pattern of marriage occurs among social strata. If a man derived from tana’ bulaan or tana’ bassi family will marry a woman from tana’ karurung and tana’ kua-kua, then their descendants will become the descendants of tana’ bulaan and tana’ bassi or aristocrats. On the other hand, if a woman from tana’ bulaan or tana’ bassi marries a man from tana’ karurung or tana’ kua-kua, then their descendants will no longer be aristocrats even though they still have royal blood. 2) The impact of the shift in wedding traditions covers positive and negative. (a) the positive impacts are marriage does not longer rely on social class, anyone can find his / her own partner, and everyone is allowed to take care of it in the government system without involving the wider community. (b) the negative impact is the waning of the value and meaning of the rampanan kapa’ custom; many people do not care about the Toraja custom anymore, especially in the wedding tradition.